Transnational Management-Consulting Firms in Thailand and ASEAN - Qadeer Hussain; Hafiz Mirza (Malaysian Management Journal, 2020)
The expansion and global role of management consulting services have become a topic of some interest in the context of the internationalization of services. The objectives, motivations, and strategies of Transnational Management-Consulting Firms (TMCFs) in the Thai market is the core subject of this paper. In addition, this paper presents performance and operational aspects of TMCFs in Thailand. Since TMCFs may enter foreign markets through a number of entry modes, their entry mode preferences in this market are analyzed in the context of their objectives, and local and regional conditions. This analysis is based on a recently completed interview-based survey of TMCFs in Thailand and is therefore a timely examination of a crucial subject—especially given the ongoing debate about "Services and Development". Firm, home and host-country related and international factors are separately identified and their interactions discussed. The future prospects for TMCFs in Thailand and ASEAN are also discussed.